Measurement of sigma (psi(3770) to proton antiproton neutral pion) and determination of sigma (proton antiproton to psi(3770)neutral pion) for the PANDA experiment - Ullrich, Matthias Gunter; Justus Liebig University Giessen (My University, 2013)
The cross section of the decay psi(3770) to proton antiproton and neutral pion has been measured and the cross section of proton antiproton to psi(3770) and neutral pion has been determined. Dector simulation software for the simulation of a time of flight detector upgrade for the BESIII experiement has been developed and tested, as well.The improvement in pion and kaon separation is estiamted.

Der Wirkungsquerschnitt des Zerfalls Psi(3770) nach Proton Antiproton und neutrales Pion wurde gemessen und der Wirkungsquerschnitt der Reaktion Proton Antiproton nach Psi(3770) und einem neutralen Pion wurde bestimmt.Des Weiteren wurde Detektorsimulationssoftware für ein Flugzeitdetektorupgrade für das BESIII Experiment entwickelt und die verbesserte Pion und Kaon Diskrimination ermittelt.
Messsung von sigma (psi(3770)nach proton antiproton neutrales pion) und Bestimmung von sigma (proton antiproton nach psi(3770)neutrales pion) für das PANDA Experiment
Keywords: ddc:530